Detection of Staphylococcal Exotoxins in Antrochoanal Polyps and Chronic Rhinosinusitis with Nasal Polyps. Issue 2 (30th October 2012) - Guven, Mehmet; Karabay, Oguz; Akidil, Oznur; Yilmaz, Mahmut Sinan; Yildirim, Muzaffer
Abstract : Objective: Staphylococcal exotoxins have been reported in the pathogenesis of many chronic inflammatory diseases. Recent reports have hypothesized that staphylococcal exotoxins might be related to inflammatory mucosal changes seen in chronic sinusitis with nasal polyps (CRS‐NPs). Staphylococcal exotoxins have the capacity to act as superantigens (SAgs), bypassing normal antigen processing and directly stimulating a massive inflammatory response. The objective of this study was to analyze polyp tissue samples from patients with antrochoanal polyps (ACPs) and CRS‐NPs for the presence of staphylococcal exotoxins. Study Design: Prospective cohort study. Setting: Tertiary medical center. Subjects and Methods: Tissue samples were obtained from 29 patients and 16 controls. Thirteen of 29 patients had ACPs, and 16 had CRS‐NPs. Specimens were analyzed for the presence of 5 staphylococcal exotoxins (SEA, SEB, SEC, SED, and toxic shock syndrome toxin–1) using enzyme‐linked immunosorbent assay (ELISA). Results: At least 1 toxin was detected in 7 of 13 patients with ACPs and in 13 of 16 patients with CRS‐NPs, whereas it was detected in only 4 controls. There were no statistically significant differences between ACP and control groups ( P =. 063). Our results showed a statistically significant association between toxin detection and patients with CRS‐NPs ( P =. 003). Conclusion: Inflammatory triggers in ACP remain a subject of debate, and this study does not support the hypothesis that staphylococcal exotoxins may play a role in ACP ethiopathogenesis. Our research is consistent with the possibility of SAgs as etiological agents in the development of bilateral nasal polyposis.